MTBP enhances the activation of transcription factor ETS-1 and promotes the proliferation of hepatocellular carcinoma cells - Wang, Hongbo; Chu, Fang; Zhijie, Li; Bi, Qian; Lixin, Li; Zhuang, Yunlong; Xiaofeng, Zhang; Niu, Xiaofeng; Zhang, Dali; Xi, He; Li, Bo-an (Frontiers in Oncology, 2022)
Increasing evidence indicates that the oncoprotein murine double minute (MDM2) binding protein (MTBP) can be considered a pro-oncogene of human malignancies; however, its function and mechanisms in hepatocellular carcinoma (HCC) are still not clear. In the present work, our results demonstrate that MTBP could function as a co-activator of transcription factor E26 transformation-specific sequence (ETS-1), which plays an important role in HCC cell proliferation and/or metastasis and promotes proliferation of HCC cells. Using luciferase and real-time polymerase chain reaction (qPCR) assays, MTBP was found to enhance the transcription factor activation of ETS-1. The results from chromatin co-immunoprecipitation showed that MTBP enhanced the recruitment of ETS-1 to its downstream gene’s (mmp1’s) promoter region with ETS-1 binding sites. In cellular and nude mice models, overexpression of MTBP was shown to promote the proliferation of MHCC97-L cells with low endogenous MTBP levels, whereas the knockdown of MTBP led to inhibition of the proliferation of MHCC97-H cells that possessed high endogenous levels of MTBP. The effect of MTBP on ETS-1 was confirmed in the clinical specimens; the expression of MTBP was positively correlated with the downstream genes of ETS-1, mmp3, mmp9, and uPA. Therefore, by establishing the role of MTBP as a novel co-activator of ETS-1, this work expands our knowledge of MTBP or ETS-1 and helps to provide new ideas concerning HCC-related research.